Recent Progress on the Synthesis of CF2H-Containing Derivatives - Levi, Noam; Amir, Dafna; Gershonov, Eytan; Zafrani, Yossi (Synthesis, 2019)
Recent years have witnessed a growing interest in the development of novel synthetic methods and new reagents for the synthesis of difluoromethylated compounds. Dozens of studies have been published on this topic each year over the past few years. These studies are focused on direct and indirect difluoromethylation of various organic functionalities via nucleophilic-, electrophilic-, radical-, carbene- or metal-mediated mechanisms. The present short review covers the very recent studies, published between mid-2017 and early 2019, on the synthesis of compounds containing a CF2H group. A brief summary of the physicochemical properties and medicinal applications of difluoromethylated compounds is also included.1 Introduction2 Nucleophilic Difluoromethylation2.1 Metal-Mediated Nucleophilic Difluoromethylation2.2 Non-Metal Difluoromethyl Nucleophiles3 Radical Difluoromethylation3.1 Metal-Induced Radical Difluoromethylation3.2 Non-Metal-Induced Radical Difluoromethylation3.3 Electrochemically Induced Radical Difluoromethylation4 Carbene-Based Difluoromethylation4.1 Metal-Induced Carbene Difluoromethylation4.2 Non-Metal-Induced Difluoromethyl Carbenes5 Cross-Coupling Difluoromethylation5.1 Palladium-Catalyzed Difluoromethylation5.2 Nickel-Catalyzed Difluoromethylation5.3 Copper-Mediated Difluoromethylation5.4 Iron-Catalyzed Difluoromethylation5.5 Gold-Mediated Difluoromethylation6 Electrophilic Difluoromethylation7 Other Examples7.1 A Difluoromethyl-Borane Complex7.2 A Tellurium Difluoromethyl Derivative8 Summary
Keywords: difluoromethylation; difluoromethylated compounds; nucleophiles; radicals; electrochemistry; carbenes